Growth responses of sacha inchi (Plukenetia volubilis L.) to eco-enzyme and arbuscular mychorriza treatments on inceptisol - Rosnina A G; Zurrahmi Wirda; Baidhawi Baidhawi; Sutiharni Sutiharni; Ali Rahmat (Open Global Scientific Journal, 2023)
The sacha inchi plant (Plukenetia volubilis L.) produces seeds with high protein content that are beneficial for human health. The planting of sacha inchi on sub-optimal land, such as inceptisol soil, requires eco-enzyme, an organic fertilizer made from environmentally friendly fermented fruit waste. In addition, the use of biological agents, such as arbuscular mycorrhiza, can increase the plant’s ability to absorb macronutrients, such as potassium and phosphorus, from the soil. This study aims to determine the effect of eco-enzyme and mycorrhiza treatments on the growth of sacha inchi plants on inceptisol. A two-factor group randomized design with nine treatments and three replications was employed. The first factor was the concentration of eco-enzyme (0 ml/l, 22.5 ml/l, and 30 ml/l). The second factor was the dose of mycofer (substance containing mycorrhizal spores) (0 g/plant, 30 g/plant, and 40 g/plant). Parameters measured were plant height, number of leaves, root length, root fresh weight, root dry weight, and mycorrhizal infection. The results show that the application of eco-enzyme was able to increase the height of sacha inchi plants in the vegetative phase at 10 and 20 days after planting (DAP) and increase the number of leaves at 30 and 40 DAP. Single application of 40 g/plant of mycofer was able to increase the vegetative growth of sacha inchi on inceptisol. The optimum amount to increase the growth rate of sacha inchi plants was reached through the combination of eco-enzyme at a concentration of 22.5 ml/l and mycofer at a dose of 40 g/plant.